Rheology New Concepts, Applications and Methods - Durairaj, Rajkumar (IntechOpen, 2013)
This book focuses on the current research in the area of rheology. Rheological characterizations are performed on materials in order to understand the basic nature of a system, quality control of raw materials and final products. The rheological characterizations are important to study the effect of different parameters such as formulation, shelf life and temperature on the quality of final products. The book covers a broad range of rheology related topics such as microrheology, capillary rheolgical measurements, characterization of dense suspensions and numerical analysis of viscoelastic fluids.